Revealing the Interaction Mechanism Stabilizing Crystalline Cellulose Iβ by Molecular Dynamics Simulations (Journal of Fiber Bioengineering and Informatics, 2018)
Revealing the interaction mechanism of cellulose Iβ can help us to understand dissolution and modification mechanisms of cellulose fiber. In this paper, molecular dynamics simulation was used to analyze different interaction of cellulose Iβ. We found that the total interaction of Van der Waals, electrostatic and solvation energy per chain are -90:93 kcal/mol at 298 K. In order to get insight into the interaction mechanism, the energy distribution of each residue and mean interaction were analyzed. The interaction were divided into the intrachain, interchain and intersheet. The results show that Van der Waals interaction is important to stacking cellulose sheets, while the sum of electrostatic and solvation energy is also play a major role in intersheet interaction. Electrostatic energy plays a role certainly in the intrasheet interaction, and the thermal stability mechanism of intrachain is different to interchain.
Keywords: Van der Waals Interaction; Electrostatic Interaction; Cellulose Iβ; Molecular Dynamics.